Research Trends of Development on Pearl Bivalve Mollusks Based on a Bibliometric Network Analysis in the Past 25 Years - Cheng, Qichao; Hu, Wanqing; Bai, Zhiyi (Frontiers in Marine Science, 2021)
Freshwater pearl mussels and marine pearl oysters are major producers of cultured pearls. With the development of pearl farming, pearl bivalve mollusks have attracted significant research attention over the past 25 years. To provide an overview of this research, we conducted a bibliometric analysis of publications from the Web of Science Core Collection database from 1995 to 2020. A network map generated by VOSviewer software was used to evaluate studies of pearl bivalve mollusks in terms of author, country, organization, journal, and keywords. A total of 2288 publications were obtained, showing an annual increase in the number of papers. Researchers based in China were a major contributor to the field and there was active cooperation among authors. Research focused on mussel and oyster developmental biology, growth, culture mode, molecular biology, and ecological conservation. In recent years, hot topics, such as growth performance and traits, pearl formation and biomineralization, and immune response have been widely discussed. Genomics, transcriptomics, proteomics, and metabonomics analyses were commonly used to analyze the regulatory mechanism of coding and noncoding genes. The interaction between the environment and farming activities showed the importance of sustainable development. Interdisciplinary research could solve some of the issues facing the pearl bivalve mollusk farming. In conclusion, our findings could serve as another way to understand research trends in pearl bivalve mollusks and contribute to future studies.